2003
DOI: 10.1063/1.1537878
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of fluorescence-based imaging of high-energy-density hydrodynamics experiments

Abstract: Experiments conducted on the LANL Trident two-beam facility show the viability of fluorescence-based imaging as a diagnostic in high-energy-density (HED) hydrodynamics experiments. Passive fluorescence experiments using titanium-pumped scandium-oxide, or iron-pumped manganese-oxide, show that fluorescence emission can be produced at sufficient intensities to be useful. Dynamic experiments, designed to demonstrate particle tracking in time for particle imaging velocimetry (PIV), were marginally successful in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…However, the results were unreliable because bubbles of different sizes are distributed randomly in the liquid medium. To overcome this problem, the reactor media is seeded with fluorescent tracers (Kumar et al, 2007;Lanier et al, 2003). Boldo et al (2004) reported the use of the PIV measurement approach to determine liquid circulation velocity and vibration amplitude using the time-averaging holography method.…”
Section: Understanding Cavitational Activitymentioning
confidence: 99%
“…However, the results were unreliable because bubbles of different sizes are distributed randomly in the liquid medium. To overcome this problem, the reactor media is seeded with fluorescent tracers (Kumar et al, 2007;Lanier et al, 2003). Boldo et al (2004) reported the use of the PIV measurement approach to determine liquid circulation velocity and vibration amplitude using the time-averaging holography method.…”
Section: Understanding Cavitational Activitymentioning
confidence: 99%
“…XRFI has previously been considered as a diagnostic for high energy density experiments 2 and a previous experiment a) Contributed paper, published as part of the Proceedings of the 20th Topical Conference on High-Temperature Plasma Diagnostics, Atlanta, Georgia, USA, June 2014. b) macdonm@umich.edu by Lanier et al 3 showed that x-ray fluorescence signals can be imaged, but no shock was observed due to the large dopant particles used. Here we present the results from experiments at the Trident Laser Facility at Los Alamos National Lab 4 using XRFI to image a shock in a planar geometry.…”
Section: Introductionmentioning
confidence: 97%
“…This technique is known as particle imaging velocimetry (PIV), which is commonly used in fluid flow experiments [3]. Previous studies have had difficulties producing dopant granules small enough to move freely with the flowing material, a condition known as hydrodynamic invisibility [4]. Achieving hydrodynamic invisibility will require smaller dopant granules, in turn requiring an imaging system with higher spatial resolution to track individual particles.…”
Section: Flow Velocity Via Particle Imaging Velocimetrymentioning
confidence: 99%
“…t the photoabsorption the several-keV range n the scattering cross DP experiment by inpant. Developing this rammatic applications aging in NIF hydrodynamic experiments [4] to cross validation of temfrom x-ray Thomson scattering [5]. ty system by induced fluorescence was first proposed by Lanier et al [6].…”
Section: D Targetmentioning
confidence: 99%
See 1 more Smart Citation